Antimicrobial resistance profiles of human Brucella melitensis isolates in three different microdilution broths: the first multicentre study in Bosnia and Herzegovina - Arapović, Jurica; Kompes, Gordan; Dedić, Kanita; Teskeredžić, Sanela; Ostojić, Maja; Travar, Maja; Tihić, Nijaz; Delić, Jasminka; Skočibušić, Siniša; Zekiri-Sivro, Minela; Verhaz, Antonija; Piljić, Dilista; et al. (Elsevier BV, 2022)
Background : Brucellosis is a ubiquitous emergent bacterial zoonotic disease causing significant human morbidity in Bosnia and Herzegovina. So far, a high rate of resistant Brucella has been found worldwide. This study prospectively analysed the rates of resistance among human Brucella melitensis (B. melitensis) strains isolated in Bosnia and Herzegovina. Methods : This study included 108 B. melitensis isolates from 209 patients diagnosed at five medical centres in Bosnia and Herzegovina. The resistance profiles of the B. melitensis isolates for the 13 most commonly used antimicrobials were studied in standard Brucella broth (BB) and cation–adjusted Mueller–Hinton broth (CAMHB) supplemented with 4% lysed horse blood or 5% defibrinated sheep blood. Results : Of the 209 patients, B. melitensis blood cultures were positive for 111 (53.1%). Among the 108 isolates investigated, 91 (84.3%) were resistant to trimethoprim–sulfamethoxazole on BB, but not on either CAMHB. Nearly all isolates (>90%) were resistant to azithromycin on BB and both CAMHBs. Conclusions : We observed a high rate of B. melitensis resistance to azithromycin. The high rate of resistance to trimethoprim–sulfamethoxazole that we observed was related to BB, so an alternative broth should be used, such as the enriched CAMHBs in this study, for evaluating resistance to trimethoprim–sulfamethoxazole. Whole–genome sequencing studies are needed to understand the development of antimicrobial resistance in B. melitensis strains isolated from humans.